The relationship between perceived promotion of autonomy/dependence and pain-related disability in older adults with chronic pain: the mediating role of self-reported physical functioning - Matos, M.; Bernardes, S. F.; Goubert, L. (Journal of Behavioral Medicine, 2016)
Chronic pain is prevalent among older adults and is usually associated with high levels of functional disability. Social support for the promotion of functional autonomy and dependence has been associated with pain-related disability and self-reported physical functioning. Nevertheless, these relationships need further inquiry. Our aims were to investigate: (1) the relationship between perceived promotion of autonomy/dependence and pain-related disability and (2) the extent to which self-reported physical functioning mediated these relationships. 118 older adults (Mage = 81.0) with musculoskeletal chronic pain completed the Portuguese versions of the revised formal social support for Autonomy and Dependence in Pain Inventory, the pain severity and interference scales of the Brief Pain Inventory, and the physical functioning scale of the Medical Outcomes Study-Short-Form 36 v2. Higher levels of perceived promotion of autonomy were associated with lower pain-related disability; this relationship was partially mediated by self-reported physical functioning (B = -.767, p < .001 decreasing to B' = -.485, p < .01). Higher perceived promotion of dependence was associated with higher pain-related disability; this effect was also partially accounted for by self-reported physical functioning (B = .889, p < .01 decreasing to B' = .597, p < .05). These results highlight the importance of perceived promotion of autonomy and dependence for managing older adults' experience of chronic pain.